HSK 以外的汉语新词汇分类 - Wu Liangyu; Low Hiang Loon; Goh Ying Soon (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
As the number of new Chinese vocabulary increases year by year, mastering new vocabulary beyond the HSK (Global Chinese Proficiency Test) syllabus is crucial to improving the overall language proficiency of international students. However, international students face many challenges in understanding new Chinese vocabulary, including emotional tendencies, personal abilities, and the complexity of Chinese vocabulary. Among them, the biggest challenge comes from the aspect of vocabulary. Specifically, the most prominent problems faced by international students in learning new Chinese vocabulary include the complexity of vocabulary, the lack of a systematic learning method, the difficulty in identifying vocabulary with multiple meanings, and the difficulty in inferring their meaning based on existing knowledge. Therefore, it is particularly important to systematically learn the classification and characteristics of new Chinese vocabulary. Based on the two dictionaries of